Breast cancer screening practices among Afghan women visiting Istiqlal and Jumhuriat hospitals in Kabul city, Afghanistan - Mudaber, Mohammad Jawad; Mehmet, Nimetcan (International Journal of Research in Medical Sciences, 2020)
Background:The Incidence of breast cancer is rising in developed and developing countries. Early detection, screening, awareness of early signs, and symptoms are critical to improve breast cancer by seeking diagnosis and treatment. The aim of this study is to examine practices regarding breast cancer among Afghan women, visiting Istiqlal and Jumhuriat hospitals in Kabul city. Methods:A cross-sectional descriptive study was conducted among 410 Afghan women aged 18 years and above who visited Istiqlal and Jumhuriat national hospitals in Kabul city, Afghanistan. The data was collected using self-administrative methods and face to face interviews from February to March 2020. A standard questionnaire was used for the study and it was translated from the English language to Pashto and Dari languages. The data was analyzed using SPSS version 24. Results: The majority of Afghan women who participated in this study had weak screening practices of breast cancer. Only 27.6% of participants were practicing breast self-examination, 14.9% of them practiced clinical breast examination during the past one year and 13.9% of them performed mammograms in the past 2 years. The commonest reason for not practicing breast self-examination was that they have never taught how to perform breast self-examination. The reason for not performing clinical breast examination was that they were shy to go for clinical breast examination and the other common reason was that the clinics were far from them. The education level had a significant association with their practices of breast self-examination (p=0.001) and clinical breast examination (p=0.031). <span style="font-size: 11.0pt; line-height: 115%; font-family: ’Calibri’,sans-serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Calibri’,sans-serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Overall the findings of this study indicate that Afghan women who participated in this study had weak practices of breast cancer screening. It is important to increase future screening programs and improve the awareness level about screening methods of breast cancer among Afghan women through appropriate health education campaigns Background:The Incidence of breast cancer is rising in developed and developing countries. Early detection, screening, awareness of early signs, and symptoms are critical to improve breast cancer by seeking diagnosis and treatment. The aim of this study is to examine practices regarding breast cancer among Afghan women, visiting Istiqlal and Jumhuriat hospitals in Kabul city. Methods:A cross-sectional descriptive study was conducted among 410 Afghan women aged 18 years and above who visited Istiqlal and Jumhuriat national hospitals in Kabul city, Afghanistan. The data was collected using self-administrative methods and face to face interviews from February to March 2020. A standard questionnaire was used for the study and it was translated from the English language to Pashto and Dari languages. The data was analyzed using SPSS version 24. Results: The majority of Afghan women who participated in this study had weak screening practices of breast cancer. Only 27.6% of participants were practicing breast self-examination, 14.9% of them practiced clinical breast examination during the past one year and 13.9% of them performed mammograms in the past 2 years. The commonest reason for not practicing breast self-examination was that they have never taught how to perform breast self-examination. The reason for not performing clinical breast examination was that they were shy to go for clinical breast examination and the other common reason was that the clinics were far from them. The education level had a significant association with their practices of breast self-examination (p=0.001) and clinical breast examination (p=0.031). <span style="font-size: 11.0pt; line-height: 115%; font-family: ’Calibri’,sans-serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Calibri’,sans-serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Overall the findings of this study indicate that Afghan women who participated in this study had weak practices of breast cancer screening. It is important to increase future screening programs and improve the awareness level about screening methods of breast cancer among Afghan women through appropriate health education campaigns